TRPs in Ovarian Serous Cystadenocarcinoma: The Expression Patterns, Prognostic Roles, and Potential Therapeutic Targets - Zhang, Cheng; Xu, Cong; Ma, Chuanshun; Zhang, Qinghua; Bu, Siyuan; Zhang, Dao-Lai; Yu, Liting; Wang, Hongmei (Frontiers in Molecular Biosciences, 2022)
Ovarian cancer (usually Ovarian serous cystadenocarcinoma, OV) is the fifth leading cause of women’s cancer-related deaths, which causes more than 184000 deaths of women worldwide annually, and it is still a highly lethal malignancy. However, the mechanism of etiology remains unclear. The lack of prognostic and diagnostic biomarkers are the main restrictions for clinical diagnosis and treatment. The transient receptor potential (TRP) channels play essential roles in the occurrence and development of cancers which may have the potential as a therapeutic target for OV. In our study, we used bioinformatic methods to study the potential effect and function of the TRP family in patients with OV. Differential expression analysis showed that the expression of TRPC7, TRPV4, and other TRP family members was significantly different between tumor and normal tissues. Through survival analysis, we screened out that the high expression of TRPC7, TRPV4, and TRPM (2,4,8) was negatively correlated with the prognosis of patients. In contrast, the low expression of TRPM3 was negatively associated with the prognosis. Cox regression analysis further indicated that TRPV4 was OV's most likely therapeutic target. Finally, we conducted mRNA expression analysis, functional enrichment analysis, and immune infiltration analysis to confirm that TRPV4 was the most convincing therapeutic target of OV.